Ecological Situation of Schools of Northern Lithuania - Volodka, Henrikas (Acta Paedagogica Vilnensia, 2001)
The ecological situation of special schools has not been fully investigated. Moreover, society isn’t informed about the results of surveys. The subsequent problems of schools of Northern Lithuania are: 1. First and urgent dilemma is bad geographical location of schools. It is necessary to underline that the majority of schools are near the congested streets, there is high percentage of air pollution, smog and it’s very noisy. 2. Secondary a part of schools doesn’t apply to the norms of sanitation. Indeed, bad light in classes, out of use sanitarian jooi11ts, tables used not according to the age of students cause profound health problems. 3. Third problem is that some schools have old heating equipment, no flora variety, etc. (the majority of trees are birches, spruces, linden).